THE DEVELOPMENT OF MATHEMATICS TEACHING AND LEARNING PROCESS: AN APPLICATION OF ACTION RESEARCH - Mohamad Rif'at; Soleh Khalimi (Bestari: Jurnal Pendidikan dan Kebudayaan, 2020)
Abstract.  The purpose is to implement action research in mathematics teaching and learning process. The questions addressed are: (1) Is the teaching and learning process compatible with the management standard? And (2) how does the teaching and learning process influence the ability to handle varies needs of students? The research procedure is the researcher observed by the lecturers of mathematics through survey about the knowledge and experience based on the standard. The implementation directed at improving student learning outcomes and the improvements to the didactical, methodical and pedagogical components. Through the research activity: (1) directly involved in providing action; (2) to learn and apply the knowledge and thoughts; (3) get social measures; (4) openly justified biases to students; (5) get a permanent effect on the groups; and (6)  to contribute to the desired changes.The data is qualitative and quantitative and analyzed descriptively. The results are: (a) the compatible with teaching standard, i.e., more benefit, practical, valid and reliable and (b) the teaching and learning process accomodated to vary of the student needs.Keywords: action research; compatible; didactical; pedagogical; methodical